Antimelanoma and Antityrosinase from Alpinia galangal Constituents - Chih-Yu Lo; Po-Len Liu; Li-Ching Lin; Yen-Ting Chen; You-Cheng Hseu; Zhi-Hong Wen; Hui-Min Wang (The Scientific World Journal)
Two compounds, 1,7-bis(4-hydroxyphenyl)-1,4,6-heptatrien-3-one (BHPHTO) and bisdemethoxycurcumin (BDMC) they have been isolated from the rhizomes of Alpinia galangal, and the structures of both pure constituents were determined using spectroscopic analyses. The study examined the bioeffectivenesses of the two compounds on the human melanoma A2058 and showed that significantly inhibited the proliferation of melanoma cells in the cell viability assay. This research was also taken on the tests to B16-F10 cell line and showed minor inhibitory consequences of cellular tyrosinase activities and melanin contents. Our results revealed the anticancer effects of A. galangal compounds, and therefore, the target compounds could be potentially applied in the therapeutic application and the food industry.